Possibilities and perspectives of modern SPA therapies for developing a healthy lifestyle (Research Announcements "Heritage BG", 2025)
This article draws attention to the possibilities of applying modern spa therapies in order to reduce the risk of socially significant diseases, perspectives for the development of wellness education and future research. The results of recent studies on the effectiveness of spa and wellness programs in influencing psycho-emotional state, overweight, cellulite and health in users of these services are analyzed. References:Alexandrova 2019: Alexandrova, Velichka. Efektivni uelbiing metodi vav vodna sreda pri zheni sas zatlastyavane v sredna vazrast. Smart inovatsii v rekreativnata (Wellness) industria i nishov turizam. Mezhdunarodno nauchno spisanie. Rekreativna & Wellness Industria i Nishov Turizam, (1), ISSN: 2603-493X, 49-53.Andonova 2014c: Andonova, Tatyana. Metodika za namalyavane na stresa i trevozhnostta. Sport i nauka, (4), 103–107.Marinova 2018: Marinova, Denka. Vliyanie na traditsionniya kitayski masazh (tuyna) varhu kachestvoto na zhivot pri patsienti s mnozhestvena skleroza. Elektronno spisanie Manas, Tsentar na iztochni ezitsi i kulturi „Sv. Kliment Ohridski“, Sofia: 4(2), ISSN 2376 -6256 (online), 205-213.Marinova 2019: Marinova, Denka. Prouchvane efekta na terapevtichniya masazh pri patsienti s hronichna bolka v shiyniya dyal. Sbornik s dokladi, Mezhdunaroden nauchen kongres „Prilozhni sportni nauki“. NSA PRES, ISBN: (Online): 978-954-718-601-9, ISBN: (Print): 978-954-718-602-6, 581-585.Nikolovska, Krstev, Megova, Mihaylova 2013: Nikolovska, Lence,Toshe Krstev, Tanya Megova, N. Mihaylova. Dvigatelynaya programa dlya reduktsii masyi tela pri zbyitochnom vese i tsellyulite. Materialyy II Vserosiyskoy nauchno prakticheskoy konferentsii s mezhdunarodnyim uchastiem: „Lechebnaya fizicheskaya kulytura: dostizhenia i perspektivyi razvitia“ (27-28 MAYA 2013г.). 88-191.Popova-Dobreva 2012: Popova-Dobreva, Diana, Gencheva, Nezabravka. Literaturen pregled na publikacii, svarzani s Wellness & Aromatherapy; Sport i nauka, Sofia, Izvan. Br. 1, 135-141.Tomova 2022: Tomova, Tatyana. Traditions and innovations in the manual impacts in Recreation and Wellbeing. Lecheben massaj pri celulit. Godina II, broy 3, ISSN (Print): 2815-3138 // ISSN (Online): 2815-3316, BYULETIN „NASLEDSTVO BG“ – NAUCHNI IZVESTIA“ 2/2022, ed. Emmanuel Moutafov, Sofia, 88-93.Angelcheva, Petkova 2019: Angelcheva, Mariana, Petkova, Simona. Effects of combination between relax massage and Bach flover remedies on everyday stress, Proceedings book, International Scientific Congress ‘Applied Sports Sciences’, Balkan Scientific Congress ‘Physical Edukation, Sport, Health’, 15-16 November 2019, Sofia, Bulgaria, www.icass2019.com, ISBN(Online): 978-954-718-601-9, ISBN(Print): 978-954-718-602-6, 348-352.Angelcheva 2023: Angelcheva, Mariana. Complex SPA program effect on overweight women’s physical condition and well-being. Trakia Journal of Sciences. Series Social Sciences. ISSN 1313-3551, 21(1). Vol. 21, Suppl.1, 556-560.Angelcheva, Tomova 2023: Angelcheva, Mariana, Tatyana Tomova. Apitherapeutic Heritage – Application and Innovation in the Spa and Wellness Industry of Bulgaria, Bulletin ‘Heritage BG’ – Research Announcements 5/2023, ed. Emmanuel Moutafov, Year 3rd, issue 5th, ISSN (Print): 2815-3138 // ISSN (Online): 2815-3316, Sofia, 3(5), 66-73.Bauer et al. 2010: Bauer Brent, Susanne Cutshall, Laura Wentworth, Deborah Engen, Penny Messner, Christina Wood, Karen Brekke, Ryan Kelly, Thoralf Sundt. Effect of massage therapy on pain, anxiety, and tension after cardiac surgery: a randomized study. Complement. Ther. Clin. Pract, 16, 70-75.Bei Yang et al. 2017: Bei Yang, Qi-Zhong Qin, Ling-Li Han, Jing Lin, Yu Chen. Spa therapy (balneotherapy) relieves mental stress, sleep disorder, and general health problems in sub-healthy people. International Journal of Biometeorology. 62(5), 261-272.Brown’s, Gerbarg 2005b: Brown’s, Richard, Gerbarg Patricia. Sudarshan KriyaYogic breathing in the treatment of stress, anxiety, and depression—part II: clinical applications and guidelines. Journal of Alternative and Complementary Medicine. 11(4), 711–717.Dutheil, Chaplais, Vilmant, Courteix, et al. 2019: Dutheil, Frédéric, Elodie Chaplais, Audrey Vilmant, Daniel Courteix et al. Stress management in obesity during a thermal spa residential programme (Obesi Stress): protocol for a randomized controlled trial study, BMJ Open, 9, e027058,1-10.Haleem 2014: Haleem, Darakhshan. Investigations into the involvement of leptin in responses to stress. Behav Pharmacol, 25, 384–97.Marinov, Gencheva, Angelcheva, Ignatov, Dimitrov 2017: Marinov, Todor, Nezabravka. Gencheva, Mariana Angelcheva, Ignat Ignatov, Vasil Dimitrov. Influence of Yoga Practices on Stess Coping Strategies. Journal of Medicine, Physiology and Biophysics. ISSN 2422-8427. An International Peerreviewed Journal, 39, 57-63.Moyer 2008: Moyer Christopher. Affective massage therapy. Int. J Ther. Massage Bodyw, 1, 3-5.Nesheva 2015: Nesheva, Irina.Benefits of the physical activity and the elaborated program mental prevention gym for women with normal pregnancy. Research in Kinesiology, 43(2), 210-214.Nikolovska, Andonova, Kraydjikova, Peeva 2012: Nikolovska, Lence, Tatyana Andonova Leyla Kraydjikova, Penka Peeva. Мassage methods for psychoemotional recovery in female athletes. Sport &Science. Extra issue 2012, VІ International Scientific Congress “Sport, Stress Adaptation”, 17-19 may 2012, 694-697.Pavlova, Paskaleva, Ivanova 2016: Pavlova,Vanya, Ruska Paskaleva, Violeta Ivanova. Application of spa and wellness procedures for prevention of stress. Proceedings of the fifth scientific session for teachers and students of Medical College – Varna, October 13 – 14, 2016, 5(4), 336-341.Popova-Dobreva 2022: Popova-Dobreva, Diana. Wellness innovations and good aromatherapy practices in Bulgaria. Bulletin ‘Heritage BG’ – Research Announcements 3/2022, ed. Emmanuel Moutafov, ISSN (Print): 2815-3138 // ISSN (Online): 2815-3316. Sofia, 2(3), 98-103.Popova-Dobreva 2023: Popova-Dobreva, Diana. Wellness Innovations Basedon Bulgarian Rose, Bulletin ‘Heritage BG’ – Research Announcements 5/2023, ed. Emmanuel Moutafov, Year 3rd, issue 5th, ISSN (Print): 2815-3138 // ISSN (Online): 2815-3316, Sofia, 3(5), 74-81.Schnebelen-Berthier et al. 2019: Schnebelen-Berthier, Coralie, Nathalie Negro, Arnaud Jaruga, Christian-Francois Roques, Jean-Michel Lecerf . Long term effect of spa therapy combined with patient education program on subjects with overweight and obesity – A controlled study. Obes Res Clin Prac.,13(5), 492-498.Trendafilov, Dimitrova 2013: Trendafilov, Dimitar, Dimitrova, Bistra. Aqua spinning as anti-stress health prevention. Acts of conference ‘physical education and sport’. Montenegro, 2013, no 37-39 / XI, ISSN: 1451-485 (9771-4517-48001), 454-460.Wändell, Carlsson, Gеfvels, Andersson, Törnkvist 2012: Wändell, Per, Axel Carlsson, Catharina Gеfvels, Katarina Andersson, Lena Törnkvist. Measuring possible effect on healthrelated quality of life by tactile massage or relaxation in patients with type 2 diabetes Complement. Ther. Med., 20, 8-15.
Keywords: spa therapies; certified spa and wellness centres; wellness; education